Implementation of Design Thinking for Web Based E-Voting Student Organization in Nahdlatul Ulama University of Yogyakarta - Pipit Febriana Dewi; Abdulloh Badruzzaman; Muhammad Hanif Misbahuddin; Moh Rifqi Febriawan (Jurusan Teknik Informatika, 2022)
Purpose: implement design thinking for web based E-Voting Student Organization in Nahdlatul Ulama University of YogyakartaDesign/methodology/approach:the method which used in this research is design thinking. The steps in this method are emphatize, define, ideate, prototype, and testFindings/result:the development of E-Voting is succesfully made according to user needsOriginality/value/state of the art:E-Voting web-based for student organization in Nahdlatul Ulama University of Yogyakarta